THE EXPOSURE OF ENGLISH LANGUAGE IN EAST COAST AND WEST COAST OF PENINSULAR MALAYSIA AND ITS IMPACTS ON SOCIAL, IDENTITY AND CULTURAL BUILDING OF UNDERGRADUATE STUDENTS - Saifuddin, Anis Athira Syahirah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Malaysia, a country which is rich with cultures, languages and identities, embraced English as its second language. With English as its second language, this language also represented the language of empowerment, educational, social integration and other purposes. This paper aims to study English language exposure to the undergraduate students and its impacts on constructing their social and cultural identities as a Malaysian. Thus, Norton and Darvin’s Model of Investment is employed as the framework and thematic analysis is done on data collected by interviewing undergraduate students from East Coast of Peninsular Malaysia and West Coast of Peninsular Malaysia. The findings of this study revealed that the exposure of English language to the undergraduate students are through family, schools or educational institutions and community. However, the students from the West Coast of Malaysia added individual effort and official matters are two other methods of exposure of English language. In addition, the impacts of the exposure on their social and cultural identity can be divided into their (1) identity as a student along with their national identity and race, their (2) ideology on English language and their mother tongue which somehow shaped their social and cultural perspectives and identities, and their (3) capital on future demand from employers and experience as a consumer due to English as a tool to conduct business or transaction. Finally, this study proves that the exposure and impacts of the English language traverse beyond the surface level as they vastly influence an individual. Although Malaysians embrace their identity as a Malaysian with Malaysian values and national language, the micro scrutiny revealed more details due to the unique multicultural, multi-language, and multi identities of Malaysians.